Penerapan sistem dan prosedur akuntansi untuk perjalanan dinas berdasarkan PMK Nomor 119 Tahun 2023 pada Perwakilan BPKP Provinsi Sulawesi Utara - Sumeleh, Sifra Abigael Denisa; Sabijono , Harijanto; Kapojos , Peter M. (Yayasan Widyantara Nawasena Raharja, 2024)
Official travel is a trip outside the place of residence, either individually or together with others, to the domicile office of the civil servant or non-civil servant concerned (or PNS). It is carried out for the benefit of the state or region by order of an authorised official. This study will determine how the implementation of accounting systems and procedures for official travel at the BPKP Representative of North Sulawesi Province based on PMK Number 119 of 2023. This research employs qualitative research methods with a descriptive approach. The results demonstrate that the implementation of official travel accounting systems and procedures at the Representative of the North Sulawesi Province Financial and Development Supervisory Agency is in compliance with government accounting standards and in alignment with PMK Number 119 of 2023.